Analysis of How Active Centers Identify and Cultivate Preschool Children's Talent Based on the Lived Experience of Educators and Officials in Karaj - Samaneh Zanganeh; Marziyeh Dehghani; Mohadeseh Khattat (پژوهش‌های کاربردی روانشناختی)
The objective of the present study was to examine the lived experiences of educators and officials of talent centers in the identification and development of preschool children's talents. This study adopted a qualitative approach and a descriptive phenomenological method to examine the lived experiences of educators and officials of talent centers in the identification and development of preschool children’s talents. Institutions and talent centers in Karaj city were the sites of the investigation from 2020 to 2023. The participants were selected using a criterion sampling strategy in conjunction with a purposeful sampling procedure in the study. Semi-structured interviews were conducted with educators and officials of talent centers to collect the data. The data were analyzed using Colaizzi’s seven-step method, which revealed three primary themes (talent discovery methods, talent development programs, and suggestions for enhancing talent development) and five sub-themes. The total number of phrases was 16, with each sub-theme comprising several significant phrases. The results indicate that the most critical phase of talent identification is to enable the child to express and witness their behavior under the guidance of an expert. The findings underscore the significance of opportune cultivation, the provision of opportunities and environmental facilities, and the monitoring of intelligence changes through periodic aptitude tests in the context of talent development. The most effective approach to cultivating and utilizing the diversity of children’s talents is to improve the knowledge of parents and instructors.